2017
DOI: 10.1002/jor.23627
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐function relationships at the human spinal disc‐vertebra interface

Abstract: Damage at the intervertebral disc‐vertebra interface associates with back pain and disc herniation. However, the structural and biomechanical properties of the disc‐vertebra interface remain underexplored. We sought to measure mechanical properties and failure mechanisms, quantify architectural features, and assess structure‐function relationships at this vulnerable location. Vertebra‐disc‐vertebra specimens from human cadaver thoracic spines were scanned with micro‐computed tomography (μCT), surface speckle‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 48 publications
1
58
0
Order By: Relevance
“…All endplate defect dimensions were also in significant correlation with posterior bulging of the intervertebral discs supporting the previous observation linking lumbar disc herniation with endplate junction failure and endplate damage . There are number of studies who have reported, based from cartilaginous and bony endplates in the surgical samples of herniated discs, that the pathophysiology of lumbar disc herniation is more likely to be mechanical and the high bending movements can cause overstretching of the annular fibers which can pull off the vertebral endplate causing junctional failure and endplate damage . Another possible explanation of this phenomenon may be that dehydrated and fibrosed discs due to endplate damage are more prone to develop fissures and tears causing disc to bulge and prolapse…”
Section: Discussionmentioning
confidence: 99%
“…All endplate defect dimensions were also in significant correlation with posterior bulging of the intervertebral discs supporting the previous observation linking lumbar disc herniation with endplate junction failure and endplate damage . There are number of studies who have reported, based from cartilaginous and bony endplates in the surgical samples of herniated discs, that the pathophysiology of lumbar disc herniation is more likely to be mechanical and the high bending movements can cause overstretching of the annular fibers which can pull off the vertebral endplate causing junctional failure and endplate damage . Another possible explanation of this phenomenon may be that dehydrated and fibrosed discs due to endplate damage are more prone to develop fissures and tears causing disc to bulge and prolapse…”
Section: Discussionmentioning
confidence: 99%
“…The collagen fibers in the lamellae of the inner annulus fibrosus are continuous with the collagen fibers in the endplate, whereas the integration between collagen fibers in the nucleus pulposus and the CEP is more convoluted [7, 21]. The CEP is not structurally anchored into the BEP, and consequently the interface is easily separated: the tensile failure strength of the CEP/BEP interface is approximately 0.4 MPa where it integrates with the annulus [22]. The relatively low separation strength may reflect the loading environment at this location: in a healthy disc, the CEP/BEP interface predominately experiences compression.…”
Section: Anatomymentioning
confidence: 99%
“…At the outer annulus, the vertebral interface is formed by an enthesis – a fibrocartilaginous composite where the annular fibers are embedded into a zone of calcified cartilage that is anchored to the subchondral bone via a complex, geometric interdigitation [22]. The complex morphology and graded material properties minimize stress concentrations during complex loading that includes tension, compression, and shear forces [23, 24].…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Each IVD comprises an aggrecan‐rich core known as the nucleus pulposus (NP), 15–25 concentric sheets of aligned collagen type I encircling the NP known as the annulus fibrosus (AF), and thin layers of hyaline cartilage covering the cranial and caudal surfaces of the IVD known as the cartilage endplates (CEP) . Adjacent vertebrae interface with the IVD through the CEP, which sequesters the NP within the disc while allowing for nutrient exchange with vertebral blood vessels . The encapsulation of the NP and its anionic, dense matrix impart triphasic time‐dependence to its mechanical properties, allowing it to dissipate loads via fluid exudation and prevent harmful stress concentrations in AF and CEP through hydraulic pressurization …”
Section: Introductionmentioning
confidence: 99%